(untitled) (Annals of Medical Research, 2021)
Aim: A considerable amount of evidence is pointing out the possible contribution of neurodegeneration in the etiopathogenesis of diabetic retinopathy (DR). Materials and Methods: The evaluation and correlation of the neurodegenerative findings in the inner retinal layers with the choroid of patients with type 2 diabetes mellitus (DM) without DR via optic coherence tomography (OCT) are aimed in this study. Results: Neuronal and axonal loss seems to occur early in DM before the ophthalmoscopic vascular changes. Conclusion: Strict glycemic control, in addition to neuroprotective measures in this pre-retinopathy phase may offer a promising treatment choice by decelerating the progression to overt retinopathy.